ANALYSIS OF YOUTUBE CONTENT ‘CHANNEL: MARHABAN ACADEMY’ IN IMPROVING MUFRODAT MASTERY - Syafni, Hafidhah; Nuzula, Alfiyah Firdausi (Kitaba, 2025)
YouTube content has become a significant factor with notable effects and impacts on society today, particularly in the realms of education and learning. This is also true for Arabic language learning, where various educational contents are available to enhance learners' proficiency. The purpose of this study is to explore the "Marhaban Academy" YouTube channel, understand the vocabulary teaching methods employed, and analyze the effectiveness of its content in improving Arabic vocabulary mastery. The research adopts a qualitative descriptive approach to analyze the YouTube channel "Marhaban Academy," focusing specifically on the video titled "Learning Arabic Through Spongebob Cartoons Part 11" as a case study for enhancing vocabulary acquisition. Data collection was conducted through several stages: viewing the content, categorizing learning elements, and evaluating media usage. Data analysis involved comprehensive and detailed content review, followed by data coding based on predefined analytical categories. The findings reveal that: 1) the "Marhaban Academy" channel serves as an interactive and engaging platform for teaching Arabic; 2) three primary methods are utilized for vocabulary instruction—singing, mimicry memorization, and matching exercises; and 3) the video content employs the mimicry memorization method, which is particularly effective in enhancing learners' vocabulary mastery. These insights highlight the potential of innovative and engaging multimedia approaches in Arabic language education.